Mentoring in the library : building for the future - Lee, Marta K. (Chicago, Illinois : American Library Association, 2011)
Noted reference librarian and researcher Lee offers librarians at all levels both her experience and her ideas about establishing a formal mentoring process at the library
1. Introduction to mentoring -- 2. Mentoring internships -- 3. Mentoring and library school assignments -- 4. Mnetoring the potential librarian -- 5. Developing the neew librarian in the workplace -- 6. Mentoring for promotion -- 7. Volunteers in libraries and librarians as volunteers -- 8. Mentoring librarians electronically -- 9. Other kinds of mentoring in the library field
Includes bibliographical references (p. 111-117) and index
Keywords: Mentoring in library science -- United States